Penerapan Balanced Scorecard Sebagai Metode Implementasi Strategi Dalam Upaya Peningkatan Kinerja Universitas Timor - Rikhardus Bria Seran; Otto Randa Payangan; Sumardi Sumardi (Magister Management, Hasanuddin University, 2019)
This study aims to find out Knowing 1) the application of balance scoreCard by translating the vision, mission of the University of Timor based on four perspectives, 2) Measuring the performance of the University of Timor based on the balanced scorecard perspective. This research is qualitative research. The sample in this study was 316 respondents consisting of lecturers, students and alumni of the University of Timor and using random sampling techniques. Data were analyzed by qualitative analysis methods. The results of the study show that translating vision and mission into four perspectives (financial, customer, internal business and growth and learning) results in a balanced scorecard design which is a proposed work program at the University of Timor. While performance measurement uses four perspectives on the balanced scorecard; the customer's perspective according to students reaches 2716 points is categorized as not good. 1711 points for the lecturer's internal business perspective are said quite well. 1004 points for the perspective of growth and learning of lecturers are quite well. 1800 points for the growth and learning perspective of administrative staff are categorized quite well. 541 points for the financial perspective of University of Timor officials are also categorized quite well